#TITLE_ALTERNATIVE# - A. NUGRAHANTO (NIM : 12209089),
Downhole Water Sink (DWS) technique prove its effectiveness on dealing with water coning phenomenon which is a quite serious problem in vertical well dominated by bottom water aquifer driving force. Huge amounts of water production is one of the weakness in DWS well, hence a new study about Downhole Water Loop (DWL) is needed . Previous studies has developed an analytical equation to predict segregation flowrate of DWL. In fact, segregation rate in DWL often assessed less economic, so that analytical equation which has been developed is less effective to be applied. This study develops correlation which is able to design flow rate in order to produce optimal oil recovery. Correlation developed by performing parameters sensitivity which affect flow rate of DWL well including fluid, rock, well completion and geometry parameters of reservoir. Based on the result of validation and comparison with analytic model which has been already developed previously, shows that correlation of this study gives accurate result and can be used to predict flow rate to optimize well oil recovery up to 27% and reduce cumulative produced water to 63% which is better than the previous equation.